Replacing sedentary time or light physical activity with moderate physical activity is associated with a lower prevalence of back pain: a cross-sectional study using isotemporal analysis: Isotemporal substitution and LBP prevalence - Oliveira, Crystian B.S.; Damato, Tatiana M [UNESP]; Tebar, William R. [UNESP]; Grande, Guilherme H.D. [UNESP]; Vidal, Rubens V.C.; Ferrari, Gerson; Saraiva, Bruna T.C. [UNESP]; Christofaro, Diego G.D. [UNESP] (Elsevier, 2024)
Background: Evidence shows that lack of physical activity and sedentary time are associated with higher prevalence of low back pain (LBP). Objective: To investigate the association between replacing sedentary time and light physical activity with a higher physical activity level with the prevalence of LBP. Methods: Two hundred and sixty-six individuals from a city in southeastern Brazil were recruited to this cross-sectional study. Sedentary behavior and physical activity level were evaluated using an ActiGraph GT3X tri-axial accelerometer during 7 days. The prevalence of LBP was assessed using the Nordic questionnaire. Isotemporal substitution using logistic regression analyses were performed to investigate the association between replacing an activity with another in the prevalence of LBP. Results: Replacing time spent in sedentary behavior with moderate physical activity slightly reduced the prevalence of LBP (odds ratio [OR]= 0.97; 95% CI: 0.95, 0.98). In addition, replacing time spent in light physical activity with moderate physical activity also slightly reduced the prevalence of LBP (OR= 0.97; 95% CI: 0.95, 0.98). There was no association for replacing sedentary time and light or moderate physical activity with vigorous physical activity on the prevalence of LBP. Conclusions: The results suggest a small protective effect for LBP when replacing time in sedentary activities or light physical activity with moderate physical activity.
Keywords: Exercise; Isotemporal substitution; Low back pain; Motor behavior; Sedentary behavior